Blindness and children : an individual differences approach - Warren, David H. (Cambridge ; New York : Cambridge University Press, 1994)
"A summary and interpretation of the research literature on infants and children with visual impairments. It concludes that many aspects of delayed development are the result not of visual impairment itself, but of an environmental variables that tend to accompany visual impairment."
Introduction -- pt. I. Interaction with the physical world. Perception of the physical world -- Motor and locomotor interaction with the physical world -- Understanding the physical world -- Spatial understanding and spatial behavior -- pt. II. The acquisition of cognitive skills. Language, concept formation, and classification -- Executive functions: memory, attention, and cognitive strategies -- Cognitive style, creativity, and intelligence -- pt. III. Adapting to the social world. Social-emotional and communicative development in infancy -- Language as a social skill -- Social development and adjustment -- Developing a sense of self -- pt. IV. Summary. Longitudinal studies -- Individual differences -- Conclusion.
Includes bibliographical references (pages 337-365) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Blind children; Children with disabilities -- Development; Blindness; Child development; Infants; Children; Blindness; Child Development; Infant; Child; Enfants aveugles; Enfants handicapés -- Développement.; Cécité.; Enfants -- Développement.; Nourrissons; Enfants; Enfance; blindness; infants; children (people by age group); childhood; FAMILY & RELATIONSHIPS -- Children with Special Needs; Infants; Children; Child development; Blindness; Blind children; Children with disabilities -- Development; Kind; Entwicklung; Blindheit; Blindheid; Kinderen; Individuele verschillen; Deficientes fisicos